Intersectionality and Digital Privacy Management: A Communication Privacy Management Analysis of Revenge Porn Vulnerability in Indonesia - Fitri, Ainal; Haekal, Muhammad; Triantoro, Dony Arung (Universitas Islam Negeri Raden Intan Lampung, 2025)
This qualitative study explores the link between revenge porn incidents in Indonesia and users’ digital privacy management, integrating Communication Privacy Management (CPM) and intersectionality theories. Through semi-structured interviews with six Acehnese university students who had witnessed such cases (through first-hand observation of distributed content, and close relationships with victims), the research finds that participants had limited understanding of revenge porn and were unaware that insufficient personal data management—exacerbated by intersecting structural disadvantages—often underlies victimisation. Thematic analysis revealed failures in all five CPM principles: private information ownership, control, rules, co-ownership and guardianship, and boundary turbulence. When combined with intersecting factors such as gender, religion, technological access, and cultural conservatism, these failures increase vulnerability to online gender-based violence. Participants mainly attributed incidents to external causes (religious violations, poor parental control, inadequate sexuality education). However, they had challenges to recognize how these structural factors constrain personal agency rather than simply representing external influences. The study advances CPM theory by demonstrating that privacy management principles operate within matrices of intersecting power systems and extends intersectionality applications by specifying concrete mechanisms through which multiple oppressions shape digital privacy vulnerability. The study concludes that prevention requires comprehensive interventions: digital ownership education, culturally responsive privacy control training, explicit privacy rule negotiation in intimate relationships, responsible co-ownership management, and early boundary turbulence mitigation. The findings advance theoretical understanding of digital privacy violations as intersectional phenomena and offer practical frameworks for targeted prevention programmes that empower users while acknowledging structural constraints.